Foreign Body Causing Diagnostic Dilemma in Koch’s Abdomen Patient Presenting with Acute Intestinal Obstruction: A Case Report - Ranendra Hajong; Kamthamuon Neihsial; Arup J Baruah; Dathiadiam Tongper; Pinky Rabha (Journal of Clinical and Diagnostic Research, 2024)
The ileocaecal region is the most commonly affected region in Koch’s abdomen; however, it can involve any part of the Gastrointestinal Tract (GIT). Patients usually present late with either features of acute or subacute intestinal obstruction or with features of perforation peritonitis. Early diagnosis of abdominal Tuberculosis (TB) is still challenging due to the vague and non specific symptomatology of the disease. Hereby, the authors present a case report of 11-year-old boy who was on Antitubercular Treatment (ATT) for suspected abdominal TB, presented with features of subacute intestinal obstruction which subsequently had to be operated for acute obstruction. However, the cause of obstruction was not due to the complications of abdominal TB but due to the mechanical obstruction caused by the seeds of bayberry, which got obstructed in the relatively narrowed part of the ileocaecal region due to thickening of the bowel wall. No similar case reports have been found in the literature earlier. Hence, the present case is being reported.